Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-26551-x
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study identifies susceptibility loci for acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy with an undefined heritable risk. Here we perform a meta-analysis of three genome-wide association studies, with replication in a fourth study, incorporating a total of 4018 AML cases and 10488 controls. We identify a genome-wide significant risk locus for AML at 11q13.2 (rs4930561; P = 2.15 × 10−8; KMT5B). We also identify a genome-wide significant risk locus for the cytogenetically normal AML sub-group (N = 1287) at 6p21.32 (rs3916765; P = 1.51 × 10−… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…In addition, we found that most HLA-related genes and PDCD1 expressed at higher levels in the high-risk group, which was in accordance with the current increasing evidence regarding solid tumors suggesting that more HLA presentation increased the recognition of tumor-associated antigens in HLA and in turn increased the success of immune checkpoint inhibitor therapy ( Rizvi et al, 2015 ; Lin W. Y. et al, 2021 ). Therefore, patients with high-risk scores for AML might benefit more from immunotherapy, especially with immune checkpoint inhibitors PD-1.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found that most HLA-related genes and PDCD1 expressed at higher levels in the high-risk group, which was in accordance with the current increasing evidence regarding solid tumors suggesting that more HLA presentation increased the recognition of tumor-associated antigens in HLA and in turn increased the success of immune checkpoint inhibitor therapy ( Rizvi et al, 2015 ; Lin W. Y. et al, 2021 ). Therefore, patients with high-risk scores for AML might benefit more from immunotherapy, especially with immune checkpoint inhibitors PD-1.…”
Section: Discussionsupporting
confidence: 89%
“…It is a highly effective method for collecting information from highly correlated, complex and multiple traits through dimension reduction. Many studies have already been done which support the use of PC based GWAS for complex traits 18 , 62 64 . A comparison between the trait and PC based GWAS models suggested the use of PC based GWAS for efficient and high throughput deliverables.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a rare NDUFS8 R2C complex I variant in the germline of two AML patients was identified as heterozygous, exhibiting a decreased basal and maximal oxygen consumption rate [90]. By testing AML blood samples, 47 genes were annotated within 500 Kb of the association signal and the sentinel variant is a significant expression quantitative trait locus for 12 of these, including NDUFS8 (PBH = 1.69 × 10 −4 ) [91].…”
Section: Ndufs8 and Cancermentioning
confidence: 99%